2016
DOI: 10.1186/s12879-016-1648-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of invasive pneumococcal infections: manifestations, incidence and case fatality rate correlated to age, gender and risk factors

Abstract: BackgroundIncidence, manifestations and case-fatality rate (CFR) of invasive pneumococcal disease (IPD) vary with age and comorbidities. New vaccines, changing age distribution, prolonged survival among immunocompromised patients and improved sepsis management have created a need for an update of basic facts to inform vaccine recommendations.MethodsAge, gender and comorbidities were related to manifestations and death for 2977 consecutive patients with IPD in a Swedish region with 1.5 million inhabitants durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 42 publications
7
99
1
8
Order By: Relevance
“…The risk to die within 30 days for patients with pneumonia and any comorbidity has been reported 3.4 times higher than for patients without comorbidities, the highest relative death risk among patients with solid tumours (especially lung cancer) (Backhaus et al, 2016). The risk to die within 30 days for patients with pneumonia and any comorbidity has been reported 3.4 times higher than for patients without comorbidities, the highest relative death risk among patients with solid tumours (especially lung cancer) (Backhaus et al, 2016).…”
Section: Update Of the Recommendations Of The Italian Society Of Medimentioning
confidence: 99%
“…The risk to die within 30 days for patients with pneumonia and any comorbidity has been reported 3.4 times higher than for patients without comorbidities, the highest relative death risk among patients with solid tumours (especially lung cancer) (Backhaus et al, 2016). The risk to die within 30 days for patients with pneumonia and any comorbidity has been reported 3.4 times higher than for patients without comorbidities, the highest relative death risk among patients with solid tumours (especially lung cancer) (Backhaus et al, 2016).…”
Section: Update Of the Recommendations Of The Italian Society Of Medimentioning
confidence: 99%
“…3 The authors found high risk of both bacterial and viral diseases during the first year from MM diagnosis. 3 Backhaus et al 4 recently showed that the incidence of invasive pneumococcal disease is 154 times higher in MM patients compared to persons without MM. Augustson et al found that infections are the most common cause of death within the first 2 months from diagnosis based on data from before the introduction of novel anti-myeloma treatment and we have recently shown in a population-based study that infections are a major cause of early death in MM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Pneumococcal infections are more common and also tend to be more severe in certain populations. Young children, elderly adults, and individuals with immunodeficiency and chronic medical conditions have increased susceptibility to, and increased morbidity from, pneumococcal infections …”
Section: Introductionmentioning
confidence: 99%
“…Young children, elderly adults, and individuals with immunodeficiency and chronic medical conditions have increased susceptibility to, and increased morbidity from, pneumococcal infections. 7,8 In the late 19th and early 20th centuries before the advent of antibiotics, patients with pneumococcal infections were treated with immune serum. 9,10 Experience with serum treatments taught investigators the mechanisms of immune protection against pneumococcal infections.…”
Section: Introduction Immunoglobulin Replacement Therapymentioning
confidence: 99%